2012
DOI: 10.3238/arztebl.2012.0893
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Specialized Cancer Treatment Centers on Treatment Efficacy in Hodgkin’s Lymphoma

Abstract: The type of center and the minimum number of patients treated in a center have no impact on the treatment outcome of patients with Hodgkin's lymphoma in Germany. In all GHSG centers, regardless of type, the quality standards for successful treatment are apparently met on all levels of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…This finding is in line with previous studies (Stark et al, 2002;Engert et al, 2005;Bjorkholm et al, 2011;Evens et al, 2012;Klimm et al, 2012;Thyss et al, 2014). Although in the current study we included patients from the cancer registry with the same age range as trial patients (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in line with previous studies (Stark et al, 2002;Engert et al, 2005;Bjorkholm et al, 2011;Evens et al, 2012;Klimm et al, 2012;Thyss et al, 2014). Although in the current study we included patients from the cancer registry with the same age range as trial patients (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, centre type did not affect the risk of incorrect TGA. This is in accordance with a previous analysis by the GHSG that found no difference in the treatment outcome with regard to centre type or size (Klimm et al , ). The GHSG quality control programme as well as prompt consulting by study physicians via telephone in case of uncertainties prior to enrolment may contribute to this observation.…”
Section: Discussionsupporting
confidence: 93%
“…Considering breast cancer, however, they reported a significantly better survival for TH patients. In Germany, Klimm et al 6 analyzed center effects in the treatment of Hodgkin lymphoma but found no influence of the type of hospital or of the treatment experience.…”
Section: Resultsmentioning
confidence: 99%